Social Support Mediates the Effect of Burnout on Health in Health Care Professionals - Ruisoto, Pablo; Ramírez, Marina R.; García, Pedro A.; Paladines-Costa, Belén; Vaca, Silvia L.; Clemente-Suárez, Vicente J. (Frontiers in Psychology, 2021)
Burnout is characterized by emotional exhaustion and caused by exposure to excessive and prolonged stress related with job conditions. Moreover, burnout is highly prevalent in health care professionals. The aim of this study twofold, first, to examine the mediating role of social support over the effect of burnout in health care professionals, and second, explore potential gender differences. A convenience sample of 1035 health professionals from Ecuador, 608 physicians and 427 nurses (68% women, with and age M = 40 + 9 years old) were surveyed using Maslach Burnout Inventory (MBI), Social Support Survey (MOS) and General Health Questionnaire (GHQ-28) as measures of burnout, social support and general health respectively. Social support did mediate the negative effects of burnout in health regardless of gender. Differences across the three dimensions of burnout and health are further discussed along with their implications for designing effective burnout interventions for health care professionals in Ecuador.